Application of tissue engineering to the immune system: development of artificial lymph nodes - Cupedo, Tom; Stroock, Abraham D.; Coles, Mark C. (Frontiers in Immunology, 2012)
The goal of tissue engineering and regenerative medicine is to develop synthetic versions of human organs for transplantation, in vitro toxicology testing and to understand basic mechanisms of organ function. A variety of different approaches have been utilized to replicate the microenvironments found in lymph nodes including the use of a variety of different bio-materials, culture systems and the application of different cell types to replicate stromal networks found in vivo. Although no system engineered so far can fully replicate lymph node function, progress has been made in the development of microenvironments that can promote the initiation of protective immune responses. In this review we will explore the different approaches utilized to recreate lymph node microenvironments and the technical challenges required to recreate a fully functional immune system in vitro.